The Tectonics of the Canadian Shield - Stevenson, John S. (Heritage, 2019)
This volume, the third in a series on the Canadian Precambrian Shield presented by the Royal Society of Canada, was prepared by Fellows of the Geological Sciences Section, in response to their desire to bring up to date and to synthesize information available on the structures present in the Shield. It is a contribution to the basic understanding of the significant geological structures in the Canadian Shield. A knowledge of these features is valuable for long-range exploration and development of the extensive one deposits of gold, uranium, nickel, copper, lead, zinc, and other metals found in the Shield. It also has an importance in relations to oil structures found in rocks younger than the Precambrian, bordering the Shield. This work should be of great interest to those wishing to have a modern interpretation of Precambrian structures, especially the Canadian rocks, and to those concerned with the development of the Canadian North. It will be of special interest to practising geologists in government or industry, to university departments of geology, and to geological consultants. Royal Society of Canada "Special Publications" Series, no 4